Investigating the role of palladium electrical contacts in interactions with carbyne nanomaterial solid matter - Aleksandrova, Mariya (Frontiers in Materials, 2024)
Traps at the interface between carbyne and palladium nanocoatings, produced at different growth conditions, are explored by current-voltage characteristics, scanning electron microscopy and thermal stimulation of charges for evaluation of their nature. It was found that the Pd films can form an Ohmic contact with the carbyne at certain deposition conditions and such deviated from the Ohmic behavior according to the RF sputtering voltage. This growth parameter was found to affect the interfacial traps formation on the carbyne surface, which is important feature for the charge trapping and releasing properties for hydrogen isotopes in the context of the energy release applications. The sputtering voltages of 0.5 kV and 0.7 kV were found unsuitable for controlled trap formation. Based on the current-voltage and thermally stimulated current (TSC) measurements, a sputtering voltage of 0.9 kV appeared to be more favorable compared to 0.5 kV and 0.7 kV. At 0.9 kV thermal activation of charge carriers are enabled at lower thermal energies, showing a distinct change in TSC behavior correlated to trap activation.